Sea wife - Gaige, Amity, 1972- (Alfred A. Knopf, 2020)
"Juliet is failing to juggle motherhood and her stalled-out dissertation on confessional poetry when her husband, Michael, informs her that he wants to leave his job and buy a sailboat. With their two kids - Sybil, age seven, and George, age two - Juliet and Michael set off for Panama, where their forty-four foot sailboat awaits them. The initial result is transformative; the marriage is given a gust of energy, Juliet emerges from her depression, and the children quickly embrace the joys of being feral children at sea. Despite the stresses of being novice sailors, the family learns to crew the boat together on the ever-changing sea. The vast horizons and isolated islands offer Juliet and Michael reprieve - until they are tested by the unforeseen. Sea Wife is told in gripping dual perspectives: Juliet's first person narration, after the journey, as she struggles to come to terms with the life-changing events that unfolded at sea, and Michael's captain's log, which provides a riveting, slow-motion account of these same inexorable events, a dialogue that reveals the fault lines created by personal history and political divisions."--Publisher description.